PUOTA: FILOSOFIJOS VERTYBINĖS SĄRANGOS PROBLEMA. - Jankauskas, Skirmantas (Problems / Problemos, 2009)
Symposium could be treated as an attempt of Plato to legitimize Greek philosophy. Such a task in its turn entails a problem of the axiological arrangement of philosophy. The paper concentrates upon the speech of Socrates, which is interpreted here as an attempt to define the axiological profile of Greek philosophy. With his speech, Socrates abuts to the discussion of Symposium by making an impression of simply attempting to clarify the origin of Love. However, he relates Love to philosophizing and afterwards indulges in explicating the origin of Greek philosophizing. His considerations result in the famous conception of the 'right way'. It is affirmed here that the 'right way', marked out with the embodiments of the beautiful and initiated by the longing for the good, could be interpreted as a series of axiological landmarks of Greek philosophizing. By the analysis of the logical dynamics of the 'right way', the parallels between the constructional peculiarities of the 'right way' and the Aristotelian concept of entelechy are revealed. Another feature highlighted in the paper is the fact that Plato begins the process of isolation of philosophizing in writing. It is argued here that the fact influenced both the Platonic conception of the problem of the axiological arrangement of philosophy and its solution. In the light of this fact, the concept of truth is considered. It is maintained that truth should be considered as an inner normative landmark of philosophizing, which is isolated in writing. However, due to his syncretic skills of thinking, truth for Plato is still interrelated with virtue or, in the ontological aspect, with reality. This misleads the later post-Descartian philosophy which, despite its total isolation in thinking, still naively retains hopes for the certitude beyond thinking. It is maintained in the paper that exactly Aristotle is mostly responsible for the misleading effect, as it is he who transposed Greek philosophy entirely into writing but continued marking it with the accents of certitude, which was no longer accessible for the later philosophy.